Hydrogen production by alcoholysis of sodium borohydride. (22nd January 2013) - Ramya, K.; Dhathathreyan, K.S.; Sreenivas, J.; Kumar, S.; Narasimhan, S.
SUMMARY: Alcoholysis of sodium borohydride offers advantages due to reduction in number of steps for recycling of sodium borohydride, elimination of freezing problems that are associated with the use of water, fast generation of hydrogen, etc. Methanol was used to liberate hydrogen from sodium borohydride. The influence of the amount of solvent, substrate concentration, temperature and catalyst on the kinetics of alcoholysis reaction in non‐stabilized sodium borohydride has been examined in the present study. The reaction was found to be first order with respect to substrate concentration and zero order with respect to solvent concentration. Effect of soluble metal salts, metal powder and metal boride as catalysts on hydrogen generation rate has also been investigated. It was found that NiCl2, Ni2 B and RuCl3 were effective catalysts and hydrogen generation proceeds with high efficiency in the presence of these catalysts. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Summary Hydrogen generation studied by alcoholysis of NaBH4 with methanol Hydrogen generation occurs even at 0 °C Activation energy for alcoholysis is 26KJ/mole High efficiency was obtained with NiCl2, Ni2 B and RuCl3 catalysts